Efficacy and safety of alirocumab in people with prediabetes vs those with normoglycaemia at baseline: a pooled analysis of 10 phase III ODYSSEY clinical trials. Issue 1 (31st August 2017) - Leiter, L. A.; Müller‐Wieland, D.; Baccara‐Dinet, M. T.; Letierce, A.; Samuel, R.; Cariou, B.
Abstract: Aim: To assess the lipid‐lowering efficacy and safety of alirocumab, a proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor, in people with hypercholesterolaemia and prediabetes at baseline vs people with normoglycaemia at baseline in a pooled analysis of 10 ODYSSEY phase III trials. Methods: People classified as having prediabetes had baseline HbA1c ≥39 mmol/mol (5.7%) and <48 mmol/mol (6.5%), or two baseline fasting plasma glucose values ≥5.6 mmol/l (100 mg/dl) but no more than one fasting plasma glucose value ≥7.0 mmol/l (126 mg/dl), or had specific terms reported in their medical history; people diagnosed with diabetes at baseline were excluded, and the remainder were classified as having normoglycaemia. Participants received alirocumab or control (placebo/ezetimibe) for 24–104 weeks, with maximally tolerated statin in most cases. The primary efficacy endpoint was LDL cholesterol reductions from baseline to week 24 in the intention‐to‐treat population using the mixed‐effect model with a repeated measures approach. Results: Reductions in LDL cholesterol from baseline to week 24 with alirocumab were 44.0–61.8% (prediabetes group) and 45.8–59.5% (normoglycaemia group). In both subgroups, LDL cholesterol reductions were generally similar in those with and without baseline triglycerides ≥1.7 mmol/l (150 mg/dl). Alirocumab was not associated with changes in HbA1c or fasting plasma glucose over time in either subgroup (up to 24 months' follow‐up). Adverse event rates were generally similar in those with and without prediabetes. Conclusions: Over a mean follow‐up of 24–104 weeks, alirocumab treatment resulted in significant LDL cholesterol reductions from baseline that were similar in participants with prediabetes and those with normoglycaemia at baseline, with no effect on glycaemia and a safety profile similar to that of the control. What's new?: With statins being associated with an increased risk of diabetes (especially in individuals with risk factors for diabetes) and recent studies linking PCSK9 to glucose homeostasis, there is much interest in whether PCSK9 inhibitors affect diabetes risk. We assessed the efficacy/safety of alirocumab, a PCSK9 inhibitor, vs control over a mean follow‐up of 24–104 weeks in people with hypercholesterolaemia and prediabetes vs people with normoglycaemia at baseline from 10 ODYSSEY phase III trials. Our findings show alirocumab is generally well tolerated and significantly reduced LDL cholesterol levels to similar extents in individuals with prediabetes and those with normoglycaemia without any changes in measures of glycaemic control.